Konsep Penataan Pasar Wonokriyo Sebagai Citra Kawasan JL. Yosudarso, Kebumen - Anjas Ninda Hantari; M Ivan Triguna (Jurnal Konstruksi, 2022)
The market is a public facility for people to obtain the necessities of life. Activities that occur in the market are not only buying and selling activities but also allow for acculturation of community culture. Like the Wonokriyo Market which is a wholesale market in Kebumen Regency as a public facility that encourages the economy of the community and local government. Wonokriyo Market also has non-bus terminal facilities in it and is directly adjacent to a provincial road, namely Jalan Yosudarso. Various problems at Wonokroyo Market, such as the absence of renovation in the last ten years, undirected access to the Wonokriyo Market area, the large number of traders selling more than the size of the stalls or stalls, the lack of drainage and garbage disposal so that the market looks slum. Various problems and conditions at Wonokriyo Market, the research question is how is the concept of structuring Wonokriyo Market so that it becomes the image of the Yosudarso Street area, Kebumen? Based on the analysis in determining the structuring concept of Wonokriyo Market, it classifies issues, objectives and criteria to obtain structuring design concepts and solve problems in the field. The building period for Wonokriyo Market was designed to be a landmark that has the character of the image of Jalan Yosudarso, Kebumen.